2004
DOI: 10.1111/j.1365-2036.2004.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of erosive oesophagitis relapse with pantoprazole

Abstract: SUMMARY Aim:1To compare the safety and efficacy of pantoprazole and ranitidine in maintaining erosive oesophagitis healing. Methods: Gastro-oesophageal reflux disease patients (349) with endoscopically documented healed erosive oesophagitis (grade 0 or 1) were randomly assigned to receive pantoprazole (10, 20 or 40 mg/q.d.s.) or ranitidine (150 mg/b.d.). Erosive oesophagitis status was assessed endoscopically at months 1, 3, 6 and 12 or when relapse symptoms appeared (relapse ¼ reappearance of erosive oesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…In addition, lansoprazole prevents the recurrence of esophagitis in most patients, regardless of the degree of erosion prior to healing [20]. Other PPIs have also been compared with ranitidine as a long-term maintenance therapy for EE and, as in the current study, when administered at FDA-approved doses for maintenance therapy, they have produced significantly higher remission rates than ranitidine [21,22].…”
Section: Discussionmentioning
confidence: 73%
“…In addition, lansoprazole prevents the recurrence of esophagitis in most patients, regardless of the degree of erosion prior to healing [20]. Other PPIs have also been compared with ranitidine as a long-term maintenance therapy for EE and, as in the current study, when administered at FDA-approved doses for maintenance therapy, they have produced significantly higher remission rates than ranitidine [21,22].…”
Section: Discussionmentioning
confidence: 73%
“…rates (7,18,24). In the study by Richter et al (7), after one-year maintenance treatment with pantoprazole at the standard dose, the endoscopic recurrence rate was found to be 22%.…”
Section: S50mentioning
confidence: 99%
“…In the studies on pantoprazole, a dose of 40 mg/day was found to be superior to a dose of 20 mg/day, while a dose of 80 mg/day was found to be more effective than doses of 40 mg/day and 20 mg/day (7,8). Richter et al (7) compared 173 patients using pantoprazole 40 mg/day with 174 patients using pantoprazole 20 mg/ day.…”
mentioning
confidence: 99%
“…However, since GERD is usually not progressive, attempts to realize on-demand treatment does not appear to harm the patients [3] . For the prevention of relapse in patients with healed esophagitis, PPIs are clearly superior to H 2 -receptor antagonists, prokinetic drugs and combinations of these medications [67][68][69] . The yield between a standard dose of a PPI and one-half of this dose is, in individual studies, often small, although significant, and even probably clinically relevant differences have occasionally been observed [67] .…”
Section: Long-term Care Of Patients With Erdmentioning
confidence: 99%
“…For the prevention of relapse in patients with healed esophagitis, PPIs are clearly superior to H 2 -receptor antagonists, prokinetic drugs and combinations of these medications [67][68][69] . The yield between a standard dose of a PPI and one-half of this dose is, in individual studies, often small, although significant, and even probably clinically relevant differences have occasionally been observed [67] . On the basis of a cost effectiveness analysis using a Markov model designed to simulate the economic and clinical outcomes of GERD in relation to the cost per symptom-free patient years gained and the cost per QALY gained treatment with a standard dose of a PPI appears to be superior despite the higher drug costs [69] .…”
Section: Long-term Care Of Patients With Erdmentioning
confidence: 99%